Diversity of toxin-genotypes among Clostridium perfringens isolated from healthy and diarrheic neonatal cattle and buffalo calves. (February 2018) - Athira, Cheruplackal Karunakaran; Milton, Arockiasamy Arun Prince; Reddy, Avinash; Mekhemadhom Rajendrakumar, Arunraj; Abhishek,; Verma, Med Ram; Kumar, Ashok; Nagaleekar, Viswas Konasagara; Agarwal, Rajesh Kumar
Abstract: The diversity of toxin-genotypes of C. perfringens in neonatal calves was determined in this study. A total of 682 fresh faecal samples comprising 559 healthy and 123 diarrheic neonatal calves (cattle and buffalo) were collected from various farms in Northern India. The samples were processed for isolation of C. perfringens and toxin-genotyping by multiplex PCR. The overall prevalence of C. perfringens was 37.2%. The most predominant toxin-genotype was type A (59.7%) and the least prevalent was type C. There was no association between toxin genotypes and diarrhea of cattle and buffalo neonatal calves (P > .05). Also, 38 (14.6%) and 16 (6.1%) isolates out of the 259 carried enterotoxin ( cpe ) and beta 2 toxin ( cpb2 ) genes, respectively. Ten different toxin-genotypes were identified, and iota toxin gene was not detected in any of the sample. Highlights: High diversity of C. perfringens toxin-genotypes among diarrheic and healthy neonatal calves demonstrated. Some of the toxin- genotypes reported for the first time in neonatal calves. Prevalence of different genotypes in buffalo neonatal calves is a new addition to the knowledge. Cpe gene was found associated with C. prfringens type A, C and D isolated from neonat calves.